Jaringan Alumni sebagai Modal Sosial Pendidikan Islam: Solidaritas, Mobilitas, dan Keberlanjutan Institusi - Ahmad Dwi Juharmanto; Iftitah Hidayati; Luluk Mukarromah; M. Arjuna Umar Faruq; Rifqi Khairul Anam (Moderasi : Journal of Islamic Studies, 2026)
This article analyzes alumni networks in Islamic educational institutions as multidimensional social capital that links spiritual solidarity, graduate mobility, public da'wah, philanthropy, and the continuity of scholarly traditions. The study is grounded in the social capital theories of Bourdieu, Coleman, Putnam, Granovetter, Lin, and Nahapiet and Ghoshal, while maintaining the reflective lens of Sociology of Ereignis to read alumni networks as meaningful social events that disclose the public relevance of Islamic education. Using a qualitative library research design, this article synthesizes classical and contemporary literature on social capital, alumni engagement, pesantren, Islamic education management, and social mobility. The data were analyzed through content analysis and hermeneutic-reflective interpretation. The findings show that alumni networks perform five interrelated functions: strengthening social cohesion through bonding capital; opening career and social mobility through weak ties and conversion of capital; mediating inclusive da'wah through bridging capital; mobilizing philanthropic and humanitarian action through civic engagement; and preserving scholarly traditions while adapting to digital modernity through cultural and symbolic capital. The article also identifies internal fragmentation, politicization, weak governance, and digital communication disruption as major challenges. It concludes that alumni revitalization is not merely an administrative strategy, but a sociological and ontological necessity for sustaining the relevance, competitiveness, and public contribution of Islamic education.